Optimization of the regularization of the solution of the plate heat transfer problems - Akter, Fargana; Rakhimov, Abdumalik; Khan, Ahsan Ali; Hassan, Torla (Kulliyyah of Engineering, International Islamic University Malaysia, 2020)
Optimization of the regularization of the Fourier series in case of steady state heat transfer plate problem and heat transfer insulated plate problems are investigated and the regularization of the series solutions at a fixed point of the plates are studied at initial time and critical index.